2004
DOI: 10.1108/09526860410541522
|View full text |Cite
|
Sign up to set email alerts
|

What's important in choosing a primary care physician: an analysis of consumer response

Abstract: Given the growth of health maintenance organizations and preferred physician organizations, the purpose of this study was to determine the salient factors considered when choosing a primary care physician. A list of informational items about physicians not normally included in provider directories but which were indicated by the literature to be important were included in the survey instrument. Employees of a major state university in a south-western state were surveyed. Results indicated that at the point of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
1
21
0
1
Order By: Relevance
“…Among patients who do seek comparative data on providers, we found service-oriented criteria most strongly influenced their choice of physician, and this fits with prior research. One survey of healthcare consumers found patient satisfaction and provider accessibility to be the most important attributes when selecting a potential provider [15]. A different survey of patients seeking specialists revealed physician manner and office staff quality most influenced patient choice [1].…”
Section: Discussionmentioning
confidence: 99%
“…Among patients who do seek comparative data on providers, we found service-oriented criteria most strongly influenced their choice of physician, and this fits with prior research. One survey of healthcare consumers found patient satisfaction and provider accessibility to be the most important attributes when selecting a potential provider [15]. A different survey of patients seeking specialists revealed physician manner and office staff quality most influenced patient choice [1].…”
Section: Discussionmentioning
confidence: 99%
“…Good patient care and communication received the highest mean scores in a list of factors that patients may consider in the selection of a PCP. 17,19,20 Another factor influencing PCP choice in past studies was board certification. 16 In the current study, board certification was reported as being important to participants, with a mean score of 4.44 (on a scale of 1-5) overall.…”
Section: Discussionmentioning
confidence: 99%
“…To date, researchers have identified some factors that appear to influence choice of physician; these factors include the sex and race of the physician, whether the physician was recommended by a friend or family member, the interpersonal skills of the physician, and finally, the perceived competence of the physician. 5,[8][9][10][11][12][13][14][15][16][17] Specialty of the PCP has also been examined in previous studies. In studying which factors influence a patient's choice of a family practitioner (family medicine [FM]) or a general internist (internal medicine [IM]) as their PCP, Cherkin et al concluded that even if family practitioners and general internists were perceived to have different practice styles, the differing styles were not associated with any differences in patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Results from studies using direct questions about the respondent's preference or strength of preference for individual attributes of care have varied somewhat according to the question and attributes included. Razzouk et al 15 asked respondents to rate the usefulness of 22 different information items (including patient satisfaction ratings) for choosing a new primary care physician. They found that respondents most frequently identified ratings of patient satisfaction with care quality, access and interpersonal skills as useful information for choosing a physician.…”
Section: Introductionmentioning
confidence: 99%